(3GdGJUGd hCfXeI GdeYdheGJ (B/ s - (3HQcGJ, CMeOs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2019)
(3JYQja GdGJUGd, GdJYQa Ydi GdeYdheI , GdJYQa Ydi CfhGY GdGJUGdGJ GdGOGQjI , GdJYQa Ydi GdGJUGd GdGOGQj GdaYGd , GdJYQa Ydi WHjYI fXe GdeYdheGJ , ESJfJGL eNQLGJ fXGe GdeYdheGJ , GdJejjR Hjf GdHjGfGJ h GdeYdheGJ , GdJejjR Hjf Cge GdeNGWQ GdGdcJQhfjI , JMdjd WQb Ceff GdeYdheGJ(B.s
(3eQGLY U(B.135s
Keywords: (3GdGJUGds; (3fXe GdeYdheGJs